Factores críticos que impactan las finanzas públicas de los gobiernos locales de la región Tacna - Vilchez Olivares, Percy (2018)
The objective of the investigation is to present the causes and effects that are generated in the finances of the countries of the Tacna region, through the variables of income, expenses, investment, financing, among others. An economic and efficient management of public finances in the municipalities implies generating sufficient resources, allows for positive results in the management of funds and, in turn, allows a better quality of service that can be provided. The investigative design is deductive and systemic, for this purpose it was given to the mayors, municipal managers, accountants, in charge of the administrative and financial areas of the municipalities; with the objective of determining the factors that influence the management of public finances. The objective population was 04 provincial municipalities and 23 district municipalities that are part of the Tacna region. The results obtained indicate that in 2014, 25.93% of the municipalities in the Tacna region depend on 90% of the revenues of the central government, that is, 10% of the funds obtained from their own income, in the subject budget 29.63% of the municipalities. Regarding the budget, 29.63% of the municipalities obtained a budget deficit or surplus greater than 10%, 40.74% obtained a balance in the effective liquidation of the budget, 33.33% of the municipalities had a cost lower than 65% of the total income in investment, it is also observed that 14.81% have financial information with arrears greater than 6 months and 44.44% of municipalities do not have an elaborated and / or updated cost budget.